(untitled) (Stamford Journal of Microbiology, 2022)
Fruit juice is widely consumed everywhere in the world because of its authentic taste and is popular among both adults and children. Several studies have been conducted on common juice available in Dhaka to detect the level of microbial contamination. Consequently, the current study was done to evaluate the microbiology of a total of 25 samples and compare drinks from three different categories (street vending, packaged drinks, and soft drinks) that were collected from various locations throughout the city of Dhaka. Among all the samples fresh juice samples were found to be highly contaminated with different microbes where the total viable bacterial count was within a range of 103 to 106 CFU/ml. However, other pathogenic microbes like E. coli, Pseudomonas spp., Staphylococcus spp., Vibrio spp., and Salmonella spp. also present in fresh juice but were totally absent in other samples. The result indicates that street juice samples may be prepared under unhygienic environments and which may serve as a reservoir of various pathogenic bacteria. The study reveals that government should take necessary action to ensure public health safety. Stamford Journal of Microbiology, Vol.12 (1) 2022: 54-58